Strengthening the Islamic personality to reduce moral disengagement in Madrasah Aliyah students - Ru'iya, Sutipyo; Sutrisno; Suyadi; Supriyanto, Agus; Dewantoro, Hajar (TAWAZUN: Jurnal Pendidikan Islam, 2024)
This research is field research with quantitative research methods. This research examines two variables, namely the independent variable Islamic personality and the dependent variable moral disengagement. The aim of this research is to find out how high the level of Islamic personality of Madrasah Aliyah Negeri 2 Kulonprogo students is. How high is the level of moral disengagement of Madrasah Aliyah Negeri 2 Kulonprogo students? How big is the influence of Islamic personality on moral disengagement among students at Madrasah Aliyah Negeri 2 Kulonprogo. The research subjects were 155 students of Madrasah Aliyah Negeri 2 Kulonprogo. Data was collected through a questionnaire that refers to the Islamic personality scale which has four dimensions and moral disengagement which has eight dimensions. Data were analyzed using descriptive analysis and product moment analysis. The research results show that the level of Islamic personality of MAN Kulonprogo students is at a very high level, namely 82.5% very high and 14% high. Meanwhile, the level of moral disengagement among MAN Kulonprogo students is at a very low level, namely 62.6% very low and 29% low. The relationship between Islamic personality and moral disengagement is known from the R value = -0.286. From the R2 value to R-Square which indicates an influence of 0.082 or 8.2%. From these results it can be concluded that the higher the level of Islamic personality in MAN students, the lower their level of moral disengagement will be. Abstrak Penelitian ini adalah penelitian lapangan dengan metode penelitian kuantitatif. Penelitian ini meneliti dua variabel, yaitu variabel bebas kepribadian Islami dan variabel terikat moral disengagement. Tujuan penelitian ini adalah untuk mengetahui seberapa tinggi tingkat kepribadian Islami siswa Madrasah Aliyah Kulonprogo, seberapa tinggi tingkat moral disengagement siswa Madrasah Aliyah Kulonprogo, dan seberapa besar pengaruh kepribadian Islami terhadap moral disengagement pada siswa Madrasah Aliyah Kulonprogo. Subyek penelitian adalah siswa-siswa Madrasah Aliyah Negeri 2 Kulonprogo sebanyak 155 orang. Data dikumpulkan melalui angket yang mengacu kepada skala Islamic personality yang mempunyai empat dimensi dan moral disengagement yang mempunyai delapan dimensi. Data dianalisis dengan analisis deskriptif dan analisis product moment. Hail penelitian menunjukkan bahwa tingkat kepribadian Islami siswa MAN Kulonprogo berada pada tingkat sangat tinggi yaitu 82,5% sangat tinggi dan 14% tinggi. Sementara itu tingkat moral disengagement pada siswa MAN Kulonprogo berada pada tingkat sangat rendah yaitu 62,6% sangat rendah dan 29% rendah. Hubungan antara kepribadian Islami dengan moral disengagement diketahui dari nilai R= -0,286. Dari nilai R2 menjadi R-Square yang menandakan pengaruh sebesar 0,082 atau 8,2%. Dari hasil ini dapat disimpulkan bahwa semakin tinggi tingkat kepribadian Islami pada siswa MAN, maka akan semakin turun tingkat moral disengagement pada mereka.